2020
DOI: 10.1016/j.chb.2020.106410
|View full text |Cite
|
Sign up to set email alerts
|

Towards a cross-cultural assessment of binge-watching: Psychometric evaluation of the “watching TV series motives” and “binge-watching engagement and symptoms” questionnaires across nine languages

Abstract: In view of the growing interest regarding binge-watching (i.e., watching multiple episodes of television (TV) series in a single sitting) research, two measures were developed and validated to assess binge-watching involvement ("Binge-Watching Engagement and Symptoms Questionnaire", BWESQ) and related motivations ("Watching TV Series Motives Questionnaire", WTSMQ). To promote international and cross-cultural binge-watching research, the present article reports on the validation of these questionnaires in nine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 73 publications
0
14
0
1
Order By: Relevance
“…Indeed, individuals' adaptive reaction to negative life circumstances might be facilitated by web-related activities, which can positively contribute to alleviate negative feelings, even though sometimes paving the way for problematic online engagement (71). It has also been demonstrated that while emotional enhancement and enrichment motivation for watching TV series is more strongly related to non-problematic watching behavior, coping-escapism motive is usually more strongly associated with problematic patterns of TV series watching (32,62). Interestingly, in the current sample loss of control over TV series watching was positively predicted by anxiety symptoms and coping/escapism motivation for watching TV series, but also by emotional enhancement and social drivers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, individuals' adaptive reaction to negative life circumstances might be facilitated by web-related activities, which can positively contribute to alleviate negative feelings, even though sometimes paving the way for problematic online engagement (71). It has also been demonstrated that while emotional enhancement and enrichment motivation for watching TV series is more strongly related to non-problematic watching behavior, coping-escapism motive is usually more strongly associated with problematic patterns of TV series watching (32,62). Interestingly, in the current sample loss of control over TV series watching was positively predicted by anxiety symptoms and coping/escapism motivation for watching TV series, but also by emotional enhancement and social drivers.…”
Section: Discussionmentioning
confidence: 99%
“…The extent of TV series watching involvement and problematic binge-watching was assessed using the Italian version of the 40item Binge-Watching Engagement and Symptoms Questionnaire [BWESQ - (32); Italian version by (62)]. Relevant to the present research, only two subscales of the questionnaire were used in this study as reflecting adaptive vs. maladaptive TV series watching: engagement (e.g., "Watching TV series is one of my favorite hobbies.")…”
Section: Watching Tv Series Engagement and Loss Of Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…Even before the pandemic, escapism has been linked with internet addiction, especially as escapism allows individuals to seek comfort online ( Chen & Nath, 2016 ). For example, an aspect of internet addiction is problematic binge watching linked to loss of control, however an incentive of this is also considered to be escapism, in this case, it is a maladaptive form of coping to manage emotional problems ( Flayelle et al, 2020 ). Our study further found that loneliness, self-esteem and psychological distress predicted problematic internet use in all the four countries.…”
Section: Discussionmentioning
confidence: 99%
“…6,12,13 However, in light of the contemporary scientific debate on the risk for overpathologising everyday life, caution is required with interpreting excessive behaviours under the lens of problematic outcomes rather than a healthy and possibly positive reinforcement operated by the same behaviour. 3,4,14 Binge and problematic watching during the COVID-19 pandemic…”
Section: Addictive Versus Problematic Behavioursmentioning
confidence: 99%